Synthesis of a heat‐resistant DOPO derivative and its application as flame‐retardant in engineering plastics. Issue 22 (7th February 2017) - Xie, Mingchen; Zhang, Shimin; Ding, Yanfen; Wang, Feng; Liu, Peng; Tang, Hanying; Wang, Yintao; Yang, Mingshu
ABSTRACT: A star‐shaped DOPO derivative (GL‐3DOPO, P content 10.8 wt %) was synthesized through a two‐step reaction involving glycerol, acryloyl chloride, and DOPO. The derivative demonstrated a great improvement of thermal decomposition temperature increased to 360 °C from 194 °C (under N2 atmosphere), promoting its application in thermoplastics of high processing temperature. When blended with engineering plastics including PET, PBT, PC, PA6, and PA66 at a GL‐3DOPO loading of 25 wt %, all the compounds reached the UL94 V‐0 level and increased limit oxygen index (LOI). In PET system, LOI raised from 22.8% to 35.4% with P 2.5 wt % and passed the V‐0 test with only 0.8 P wt %. Compact char layers were found in the PET system after LOI test, suggesting that GL‐3DOPO acted both in gas and condensed‐phase mode. All results indicated that GL‐3DOPO could be a potential flame‐retardant for engineering plastics. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44892. Abstract :